Registros semióticos como estrategia didáctica para el aprendizaje de funciones valor absoluto e irracionales en primero de Bachillerato General Unificado - Solórzano Atocha, Yelitza Lizbeth (2024)
The study of functions presents difficulties for students, so it is necessary for teachers to improve their pedagogical practice with appropriate teaching strategies, such as the use of ways to represent a function. Therefore, the main objective of this research was to identify the semiotic registers as a didactic strategy for learning absolute value and irrational functions in the first year of General Unified Baccalaureate. In this sense, the type of research is descriptive documentary with a qualitative approach, where information was obtained through the bibliographic review with the use of the search log and the mixed cards. The results highlight four types of registers that present more characteristics for the study of functions, which are: algebraic, graphic, tabular, and verbal, which are used didactically with their representations and transformations, from which it is concluded that they are the most used to enhance the learning of functions. Keywords: semiotic registers, educational strategies, function, teaching strategy .